PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP HASIL PENJUALAN PRODUK BAWANG GORENG PADA UD BAWANG GORENG DI DESA PAGEDANGAN KECAMATAN ADIWERNA KABUPATEN TEGAL - Darnawi, Mrs.; Waskito, Jaka; Jalil, Mahben (PERMANA, 2018)
The purpose of this study is 1). To know the effect of promotion cost to the sale result, 2). To know the effect of distribution cost on sales result, 3). To know the effect of promotion cost and distribution cost together to the sales result. Data collection techniques used in this study is the method of documentation and interviews. While the data analysis method used is classical assumption test, simple linear regression analysis, test of simple linear regression coefficient, multiple linear regression analysis, test of multiple linear regression coefficient, coefficient of determination. Based on the results of simple linear regression analysis calculations obtained results for the promotion variable in obtaining a probability significance value of 0.000 is smaller than 0.05 means there is a significant effect of promotion on sales results concluded that the first hypothesis that reads "Suspected there is the influence of promotional costs on sales results fried onion product "proved true. The result of calculation of simple linear regression analysis obtained result for the distribution variable in obtaining the value of probability significance of 0.000 is smaller than 0,05 meaning there is significant influence of distribution to result of sale can be concluded that second hypothesis which reads "allegedly there influence of distribution cost to result of sale fried onion product "is proven. The result of simultaneous influence test obtained by the significance level of 0,000 <0,05 means there is a significant influence between the cost of promotion and distribution costs together to the sales results can be said the third hypothesis that reads "It is suspected that there is influence of promotion costs and distribution costs together. same to the sale of onion garlic products on UD Bawang Goreng in Pagedangan Village Adiwerna District Tegal Regency "proved true.Keywords: Promotion Cost, Distribution Cost, Sales Result